THE READABILITY LEVEL OF READING TEXTS IN THE ENGLISH TEXTBOOK ENTITLED WHEN ENGLISH RINGS A BELL FOR THE SEVENTH GRADE JUNIOR HIGH SCHOOL - Nurul Hikmah; Sanerita T. Olii; Ignatius J. Tuerah (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of this research is to find out the readability level of the revised version of the English textbook titled “When English Rings a Bell in Junior High School”, the aim of doing this research is to make sure the reading texts are appropriate for the student’s level of reading. In this study, students have a problem to comprehend the text well. This study use quantitative approach as the research design in this study. The data was collected using Flesch’s Reading Ease Formula. The results of the research shows that 2 texts selected from 15 texts are appropriate for the Seventh Grade of Junior High School at a “Fairly Easy” Level. There are 6 texts suitable for the fifth grade students, 4 texts suitable for sixth grade students, 3 texts suitable for eight grade students and only two reading texts appropriate for the seventh grade of Junior High School.